2014
DOI: 10.33225/pmc/14.09.213
|View full text |Cite
|
Sign up to set email alerts
|

Model of Successful Strategy Execution: Revising the Concept

Abstract: The purpose of this research is to examine the relationship between the elements of the Eight "S" model that affect strategic implementation and results achieved by companies. The main research question, to which the author sought an answer, was whether there was a relationship between individual elements that affect strategy implementation and the effects it brings in revenue growth. The survey covered 200 of the best-ranked Polish companies (where revenues constituted one of the ranking criteria) where the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…(2018), who found that sales manager transformational leadership behavior significantly and positively influenced the SI commitment of sales associates, which in turn positively impacted sales group performance. Additionally, MM leadership has been found to significantly affect the motivation of employees to implement strategic initiatives related to SIE and revenue growth (Radomska, 2014). These examples support the idea that MM leadership plays a critical role in SIE because MMs must “reinforce strategy; allocate resources for it, deal effectively with resistance to it, and convince employees that the new initiative is important and in their best interests.” (O'Reilly et al ., 2010, p. 105).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…(2018), who found that sales manager transformational leadership behavior significantly and positively influenced the SI commitment of sales associates, which in turn positively impacted sales group performance. Additionally, MM leadership has been found to significantly affect the motivation of employees to implement strategic initiatives related to SIE and revenue growth (Radomska, 2014). These examples support the idea that MM leadership plays a critical role in SIE because MMs must “reinforce strategy; allocate resources for it, deal effectively with resistance to it, and convince employees that the new initiative is important and in their best interests.” (O'Reilly et al ., 2010, p. 105).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Staffing Processes: Staff processes focus on the processes undertaken by the organization to ensure that it has the right quantity and quality of staff available. This includes processes in recruitment, training and development, rewarding and motivation (Radomska, 2014). An organization requires effective processes to ensure that it has employees with the rights skills and capabilities.…”
Section: Core Valuesmentioning
confidence: 99%